Visual detection of cyanide using ninhydrin coated paper - Syafril Hidayat; Rachadaporn Benchawattananon; Lapatrada Taemaitree (Heliyon)
Humans are often exposed to cyanide through drinking water or by eating plants that contain cyanogenic glucosides (e.g. cassava – a staple source of carbohydrates). Many methods exist to detect cyanide, but few are safe, cheap and easy to perform for an untrained user. In this work, we demonstrate that Whatman paper can be coated with ninhydrin and that the addition of basic solutions of cyanide gives an immediate pale yellow to red colour change. The ninhydrin paper can be used to visually, semi-quantitatively detect cyanide at concentrations up to ∼5 μg/mL (in 30 μL; 0.15 μg), and can be stored for several months. Most importantly, we show the paper can be used to monitor the release of cyanide from plants such as cassava leaves as they are processed in cooking suggesting the paper could be used in-the-field.